2003
DOI: 10.1007/s00234-002-0931-7
|View full text |Cite
|
Sign up to set email alerts
|

Megalencephalic leukoencephalopathy with subcortical cysts in an adult: quantitative proton MR spectroscopy and diffusion tensor MRI

Abstract: A 37-year-old macrocephalic woman was investigated for increasing gait disturbance due to longstanding spasticity and ataxia. MRI showed widespread bilateral increase in signal from cerebral white matter on T2-weighted images. Numerous subcortical cysts were visible in anterior-temporal and parietal regions. These clinical and neuroradiological features are those of megalencephalic leukoencephalopathy with subcortical cysts (MLC), a recently delineated white-matter disease with onset in childhood. Quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 20 publications
6
15
0
1
Order By: Relevance
“…Restricted diffusion pattern in Canavan's disease accounted for the histopathologic features, including edematous and gelatinous brain tissue associated with diffuse vacuolation [10] . Contrary to other vacuolating leukoencephalopathies with decreased diffusion, all 5 patients (4 children and 1 adult) with MLC reported previously showed increased diffusion and high ADC values [12][13][14] , which is in line with our adult case.…”
Section: Discussionsupporting
confidence: 78%
“…Restricted diffusion pattern in Canavan's disease accounted for the histopathologic features, including edematous and gelatinous brain tissue associated with diffuse vacuolation [10] . Contrary to other vacuolating leukoencephalopathies with decreased diffusion, all 5 patients (4 children and 1 adult) with MLC reported previously showed increased diffusion and high ADC values [12][13][14] , which is in line with our adult case.…”
Section: Discussionsupporting
confidence: 78%
“…The ADC is increased and diffusion tensor imaging data show reduced fractional anisotropy [67][68][69]. No definite hypersignal is seen within non-affected white matter structures or along the interface between normal and abnormal areas (Fig.…”
Section: Leukodystrophies Of Unknown Etiologymentioning
confidence: 93%
“…Van Der Knaap leukoencephalopathy was reported to show increased diffusion and high ADC values of the affected white matter and subcortical cysts. An increase in diffusion rates was more pronounced in the temporal cysts 3,4,7,8 . A correlation between ADC values and functional deterioration was not detected in Gelal et Al's 3 study on five patients DWI of the cases reported so far belonged to older patients (the youngest ten months and the oldest 37 years) than ours.…”
Section: Discussionmentioning
confidence: 94%